Hubungan Komunikasi Interpersonal Dengan Motivasi Kerja Karyawan Di BPJS Kesehatan Cabang Padang - Surya Ningrum; Indria Flowerina (CV. ITTC INDONESIA, 2025)
In an organization, interpersonal communication plays an important role in building effective working relationships among employees. At BPJS Kesehatan Padang Branch, the complex work dynamics demand open, empathetic, and mutually understanding communication to maintain a conducive. Work motivation plays a crucial role in determining the level of productivity and employee loyalty to the institution. This study aims to examine the relationship between interpersonal communication and employee work motivation at BPJS Kesehatan Padang Branch. Interpersonal communication is one of the key factors in creating a comfortable work environment. High work motivation is essential for employees to perform their duties optimally and contribute to achieving the organization's goals. This research uses a quantitative method with a correlational approach. Data collection was carried out through the distribution of questionnaires to 47 respondents who are active employees of BPJS Kesehatan Padang Branch. The data analysis technique used is the Pearson Product Moment correlation test to determine the relationship between variables. The results of the study show that there is a positive and significant relationship between interpersonal communication and employee work motivation. This is evidenced by the statistical test results showing a significance value of 0.000 < 0.05, indicating a positive and significant correlation. Therefore, it can be concluded that H₁ is accepted, with a correlation coefficient of 0.497, which indicates a moderate level of relationship between the variables. The better the interpersonal communication among employees, the higher their work motivation. The conclusion of this study is that interpersonal communication has a significant relationship with employee work motivation. Therefore, the institution needs to continuously encourage the establishment of open and harmonious communication in the workplace to create a more conducive work atmosphere. These findings reinforce the notion that effective and open workplace communication can enhance employee morale, loyalty, and overall performance.